Coordinated regulation of skeletal muscle mass and metabolic plasticity during recovery from disuse. Issue 1 (22nd August 2018) - Kneppers, Anita; Leermakers, Pieter; Pansters, Nicholas; Backx, Evelien; Gosker, Harry; Van Loon, Luc; Schols, Annemie; Langen, Ramon; Verdijk, Lex
ABSTRACT: Skeletal muscle regeneration after disuse is essential for muscle maintenance and involves the regulation of both mass‐ and metabolic plasticity–related processes. However, the relation between these processes during recovery from disuse remains unclear. In this study, we explored the potential interrelationship between the molecular regulation of muscle mass and oxidative metabolism during recovery from disuse. Molecular profiles were measured in biopsies from the vastus lateralis of healthy men after 1‐leg cast immobilization and after 1 wk reloading, and in mouse gastrocnemius obtained before and after hindlimb suspension and during reloading (RL‐1, ‐2, ‐3, ‐5, and ‐8 d). Cluster analysis of the human recovery response revealed correlations between myogenesis and autophagy markers in 2 clusters, which were distinguished by the presence of markers of early myogenesis, autophagosome formation, and mitochondrial turnover vs. markers of late myogenesis, autophagy initiation, and mitochondrial mass. In line with these findings, an early transient increase in B‐cell lymphoma‐2 interacting protein‐3 and sequestosome‐1 protein, and GABA type A receptor‐associated protein like‐1 protein and mRNA and a late increase in myomaker and myosin heavy chain‐8 mRNA, microtubule‐associated protein 1 light chain 3‐II:I ratio, and FUN14 domain‐containing‐1 mRNA and protein were observed in mice. In summary, the regulatory profiles of protein, mitochondrial, and myonuclear turnover are correlated and temporally associated, suggesting a coordinated regulation of muscle mass‐ and oxidative metabolism‐related processes during recovery from disuse.—Kneppers, A., Leermakers, P., Pansters, N., Backx, E., Gosker, H., van Loon, L., Schols, A., Langen, R., Verdijk, L. Coordinated regulation of skeletal muscle mass and metabolic plasticity during recovery from disuse. FASEB J. 33, 1288–1298 (2019). www.fasebj.org